The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.ajpath.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Apoptosis and in Situ Immune Response in Fatal Cases of Microcephaly Caused by Zika Virus

Abstract: Zika virus (ZIKV) is a single-stranded positive-sense RNA flavivirus that possesses a genome approximately 10.7 Kb in length. Although pro-inflammatory and anti-inflammatory cytokines and apoptotic markers belonging to the extrinsic and intrinsic pathways are suggested to be involved in fatal cases of ZIKV-induced microcephaly, their exact roles and associations are unclear. To address this, brain tissue samples were collected from 10 individuals, five of whom were diagnosed as ZIKV positive with microcephaly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 51 publications
(50 reference statements)
1
33
0
Order By: Relevance
“…ZIKV infection causes apoptosis [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. We therefore asked whether reduced innate immune recognition of ZIKV in RIG-I KO cells impacts virus-induced cell death.…”
Section: Resultsmentioning
confidence: 99%
“…ZIKV infection causes apoptosis [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. We therefore asked whether reduced innate immune recognition of ZIKV in RIG-I KO cells impacts virus-induced cell death.…”
Section: Resultsmentioning
confidence: 99%
“…First, the clinical data provide evidence that WNV infection in humans induces a significant upregulation of TNF-α. This is not surprising since previous studies in mice and cell cultures have demonstrated essential protective roles for TNF-α and other proinflammatory cytokines against acute WNV infection (10,(12)(13)(14) Moreover, high TNF-α levels have been reported in other flavivirus human infections, including dengue (21,22), Zika virus (23,24), and Japanese encephalitis virus (JEV) (25). Children infected with dengue virus showed significantly higher serum levels of TNF-α, with the highest levels in those with severe dengue disease (21), formerly "dengue shock syndrome" and "dengue hemorrhagic fever."…”
Section: Discussionmentioning
confidence: 87%
“…In fact, the potentially critical causative role of TNF-α and the associated "cytokine storm" in severe dengue disease and other viral diseases has long been recognized (26). In fatal cases of Zika fetal syndrome, a significantly increased expression of TNF-α, IFNγ, and other proinflammatory cytokines has been found in the meninges, perivascular region, and parenchyma of microcephalic brains (23,24). Japanese encephalitis virus (JEV) infection also significantly elevates expression of TNF-α and other proinflammatory cytokines in animals and cell cultures, leading to neuroinflammation and neuronal death (25).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that ZIKV infection is capable of triggering the production of proinflammatory cytokines, such as TNF and IL-β, and glutamate, mediators shown to induce neuronal cell death in ZIKV ( Olmo et al., 2017 ). Moreover, apoptosis-induced microcephaly alterations have been linked to high proinflammatory cytokines production, for instance TNFα and IL-1β ( de Sousa et al., 2018 ). In our study, when ZIKV-infected NPCs were treated BA after infection, the lower concentration of BA had a milder antiviral activity but caused less toxicity to the NPCs, protecting these cells from ZIKV-induced death.…”
Section: Discussionmentioning
confidence: 99%